Implementation of Child Birth Registration in Kampung Baru Village, Lingga Bayu District, Mandailing Natal Regency in terms of Article 27 Paragraph (1) Law Number 13 Number 24 of 2013 concerning Population Administration - Rita Annisah Lubis; Puji Kurniawan (IAIN Padangsidimpuan, 2022)
The lack of practice of registering children's births and the lack of legal knowledge regarding population identity are the background to the emergence of problems in this study. The purpose of this study was to find out how the practice of registering child births in Kampung Baru Village, Lingga Bayu District, Mandailing Natal Regency by the Department of Population and Civil Registration. As well as knowing what the inhibiting factors are in the practice of birth registration. This research is a field research using qualitative descriptive analysis method. The method of collecting data in this research is by means of interviews and documentation. The parties studied were the Department of Population and Civil Registration of Mandailing Natal Regency and one of the people in Kampung Baru Village.The results of this study prove that the Implementation of Child Birth Registration in Kampung Village from 2015 to 2016, based on article 27 paragraph (1) of Law Number 24 of 2013 concerning Population Administration has not been carried out optimally. This can be proven from the fact that there are still many people in the village who do not yet have a demographic identity in the form of a birth certificate. Judging from the fiqh siyasa of the government in the practice of registering child births in the village of Kampung Baru, it is good, it can be seen that the government in providing services, policies, and relations with the community is always based on the general benefit that the government must be prosperous for its people, trustworthy and fair to its people. Inhibiting factors in the practice of registering children's births include internal factors that come from the individual himself, such as the lack of legal knowledge of the urgency of registering the child, then external factors, and road infrastructure that seems far from the Population and Civil Registration Office of Mandailing Natal Regency.